Analisis Manajemen Layanan Preventif pada Program Nusantara Sehat di Puskesmas Waitii Kabupaten Wakatobi - salnia salnia; Sutopo Patria Jati; Farid Agushybana (Jurnal Manajemen Kesehatan Indonesia, 2022)
ABSTRACTThe use of preventive services has an effect on improving health because people who are identified as having symptoms of the disease can be detected early so that they can be anticipated immediately. Preventive services in the Nusantara Sehat program run efficiently, of course, it requires good management.The purpose and scope of the research is to raise the problem of implementing prevention services in the Nusantara Sehat program at the Waitii Health Center, Wakatobi Regency from the management program, namely planning, organizing, implementing, and monitoring the program from Nusantara Sehat on preventive services.The method used in this research is qualitative with case study design, data analysis, triangulation of sources and triangulation of findings. The research subjects were the head of the puskesmas, village head, health officer, person in charge of essential fields and the community. The data collection instrument as a guide for observations and interviews was developed from Terry's (2010) theory.The findings in this study are the management of the preventive service program implemented by the Nusantara Sehat team at the Waitii Health Center, Tomia District, for the organizational aspect, it is carried out in a structured manner starting from the way of working, division of tasks between health workers, involvement and coordination with stakeholders in preventive service activities as well as in creating cooperation with stake holders. In the implementation aspect, a motivation is applied which is reflected in the program vision. In the aspect of supervision, through a good process, starting from the criteria for setting implementation standards, determining the measurement of the implementation of activities, comparing the implementation of activities with analyzing deviations and taking corrective actions.The conclusion in this study is that all aspects of management, both planning, organizing, implementing and supervising proceed well according to Terry's theory.